Individual Characteristics, Environmental Factors, and Behavior With the Event of Dengue Hemorrhagic Fever - Amalia Rahmah Harahap; Azhari Akmal Tarigan; Putra Apriadi https://pcijournal.org/index.php/iamsph/management/importexport/plugin/QuickSubmitPlug (Pena Cendekia Insani, 2021)
Dengue hemorrhagic fever is still a serious public health problem in Indonesia. The number of dengue cases in Tebing Tinggi City is getting higher every year. This study aims to determine the relationship between individual characteristics, environmental factors and behavior with the incidence of DHF in the Tanjung Marulak Public Health Center, Tebing Tinggi City. The method used in this study is an analytical study method using a case-control study design. Analysis of research data with chi-square test. This research was conducted in the Tanjung Marulak Public Health Center, Tebing Tinggi City. From January to August 2021. The population of this study consisted of 1,457 households. The sample of this study amounted to 177 respondents. The sampling technique in the case used total sampling and the control sampling technique used gender matching. Data analysis, and discussion in the previous chapter, it can be concluded that the incidence of DHF was 59 respondents (33.3%) while those who had never contracted DHF were 118 respondents (66.7%) in the Tanjung Marulak Health Center Work Area. Cliff City. The incidence of DHF is more dominant in people aged >24 years as much as 73.4%. The majority of respondents suffering from DHF with female sex were 103 respondents (58.2%), the incidence of DHF was more dominant in respondents with low education as many as 140 respondents (79.1%) and the incidence of DHF was more dominant in respondents who worked as many as 116 respondents (65.5%). It is hoped that it can improve performance in the implementation of dengue control efforts and help establish policies and operational strategies that are efficient and effective in the implementation of dengue control in the community.